Perceived Organizational Politics, Engagement, and Stress: The Mediating Influence of Meaningful Work - Landells, Erin M.; Albrecht, Simon L. (Frontiers in Psychology, 2019)
The research aimed to assess proposed associations between organizational politics and employee engagement, employee stress, and work meaningfulness. Very few studies have examined these associations. Confirmatory factor analyses established the dimensionality and reliability of the full measurement model across two independent samples (N=303, N=373). Structural equation modelling supported the proposed direct associations between organizational politics, operationalized as a higher order construct, and employee stress and employee engagement. These relationships were shown to be partially mediated by meaningful work. As such, politics had significant indirect effects on engagement and stress through meaningful work. The results also showed a significant and direct association between stress and engagement. Overall, the results shed important new light on the factors that influence engagement, and identify work meaningfulness as an important psychological mechanism that can help explain the adverse impact of organizational politics on employee engagement and stress. The results also support the dimensionality and validity of a new set of measures of perceived organizational politics focused on generalized perceptions about the use and abuse of relationships, resources, reputation, decisions, and communication channels. More generally, the results serve as a platform for further research regarding the negative influence of organizational politics on a range of individual and organizational outcomes.